2012
DOI: 10.3892/ol.2012.1072
|View full text |Cite
|
Sign up to set email alerts
|

Magnetic resonance imaging of the brain in survivors of childhood acute lymphoblastic leukemia

Abstract: The issue of delayed neurological damage as a result of treatment is becoming increasingly important now that an increased number of children survive treatment for acute lymphoblastic leukemia (ALL). Following modification of the treatment protocols, severe symptomatic late effects are rare, and most adverse effects are detected by sensitive imaging methods such as magnetic resonance imaging (MRI) or by neuropsychological testing. In this study we aimed to determine the prevalence and characteristics of late c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
9
1

Year Published

2014
2014
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(12 citation statements)
references
References 14 publications
(15 reference statements)
2
9
1
Order By: Relevance
“…The CR rates reach up to 70 to 80%. 14 Isolated CNS relapse in ALL patients is rare as limited data are available from India on literature search. Hence an attempt was made to compile and present the data of ALL cases with isolated CNS relapse and compare the clinicopathological profile of these cases with the final outcome.…”
Section: Discussionmentioning
confidence: 99%
“…The CR rates reach up to 70 to 80%. 14 Isolated CNS relapse in ALL patients is rare as limited data are available from India on literature search. Hence an attempt was made to compile and present the data of ALL cases with isolated CNS relapse and compare the clinicopathological profile of these cases with the final outcome.…”
Section: Discussionmentioning
confidence: 99%
“…Additionally, higher plasma concentration of MTX was associated with thicker cortices in the dorsal lateral prefrontal cortex, a region involved in executive functioning ( 6 ). Brain abnormalities that were less prevalent, but still observed in ALL survivors, included cerebral microangiopathy, brain atrophy, infarcts, and hemorrhage ( 28 , 38 ).…”
Section: Resultsmentioning
confidence: 99%
“…Additional white matter abnormalities were detected by structural T1-weighted, T2-weighted, and fluid-attenuated inversion recovery MRI sequences. Five studies reported that a subset of survivors developed acute and/or persistent leukoencephalopathy ( 28 , 31–33 , 45 ), a condition associated with apparent white matter damage (ie, myelin damage) and defined by T2-weighted hyperintensity in white matter. Risk for leukoencephalopathy was highest among patients receiving more intensive therapy and higher doses of MTX ( 28 , 33 ).…”
Section: Resultsmentioning
confidence: 99%
“…Leukoencephalopathy is a characteristic complication caused by the intrathecal administration of Methothrexate, Cisplatinand, Cytarabine and Carmustine. 2 Toxic effects induced by Methothrexate are the most common in pediatric patients with leukemia. neurotoxicity can be divided into early and late leukoencephalopathy.…”
Section: Introductionmentioning
confidence: 99%